Zinc oxide embedded on chitosan/graphene oxide composite: A robust hydrophobic material for antibacterial coating - Albarqouni, Yasin M.Y.; Banius, Euodia; Thalji, Mohammad R.; Arman, Abdullah (Polska Akademia Nauk, 2025)
Organic coatings often face limitations in providing enhancement of corrosion protection in aggressive environments. This study introduces a multifunctional Graphene oxide and zinc oxide embedded in chitosan (CGZ) composite incorporated into an epoxy (EP) matrix to enhance the antibacterial activity, hydrophobicity, and corrosion resistance of carbon steel substrates. Structural and morphological characterization successfully addresses the fabrication of CGZ composite. SEM images reveal that the CGZ composite possesses a more compact and less porous structure than pure chitosan. Tafel plots also indicate that increasing the zinc oxide weight percentage in the chitosan matrix shifts the corrosion potential (Ecorr) towards more positive values, enhancing the anticorrosion performance due to the combined effects of ZnO and GO and the composite's reduced porosity. Moreover, the antibacterial testing demonstrated a moderate antibacterial effect of CGZ against E. coli and S. aureus in contrast to the zero-impact observed with pure chitosan. These findings suggest that the CGZ composite is a promising material for various applications, significantly improving chitosan alone.